Modiolus-Hugging Intracochlear Electrode Array with Shape Memory Alloy - Min, Kyou Sik; Jun, Sang Beom; Lim, Yoon Seob; Park, Se-Ik; Kim, Sung June (HINDAWI LTD, 2013)
In the cochlear implant system, the distance between spiral ganglia and the electrodes within the volume of the scala tympani cavity significantly affects the efficiency of the electrical stimulation in terms of the threshold current level and spatial selectivity. Because the spiral ganglia are situated inside the modiolus, the central axis of the cochlea, it is desirable that the electrode array hugs the modiolus to minimize the distance between the electrodes and the ganglia. In the present study, we propose a shape-memory-alloy(SMA-) embedded intracochlear electrode which gives a straight electrode a curved modiolus-hugging shape using the restoration force of the SMA as triggered by resistive heating after insertion into the cochlea. An eight-channel ball-type electrode array is fabricated with an embedded titanium-nickel SMA backbone wire. It is demonstrated that the electrode array changes its shape in a transparent plastic human cochlear model. To verify the safe insertion of the electrode array into the human cochlea, the contact pressures during insertion at the electrode tip and the contact pressures over the electrode length after insertion were calculated using a 3D finite element analysis. The results indicate that the SMA- embedded electrode is functionally and mechanically feasible for clinical applications.
Keywords: COCHLEAR IMPLANT ELECTRODES; INSERTION TRAUMA; TEMPORAL BONE; POSITION